GE_GERICHTE C/13654/2015 vom 17. Dezember 2015 - GE Cour de justice (2015)
CONDITION DE RECEVABILITÉ; CAS CLAIR; ACTION EN REVENDICATION(DROITS RÉELS); RÉPUDIATION(DROIT SUCCESSORAL) | CO.257d; CO.262; CC.573.2